The Development of Housing Market in Ukraine: Modelling and Prospects - Chevhanova, Vira; Hryhoryeva, Olesya; Khadartsev, Oleksandr (International Journal of Engineering and Technology, 2018)
Trends in the development of the housing market in Ukraine, dynamics of its fluctuations, the identification of key factors that may lead to changes and shifts in the Ukrainian housing market, the impact of the respective primary housing sectors, factors shaping the consumer preferences of households in connection with demand for housing, modeling the housing market and the prospects for the development of the housing market in Ukraine, are considered in this article. The authors pay attention to certain methodological features and factors that shape the specific functioning of the housing market in Ukraine and create the appropriate preconditions for determining the prospects for its further development. Taking into account the technical, operational, consumer and cost characteristics of such a product as housing, and the specifics of the organization and implementation of the production process in construction, the implementation of a cobweb model is proposed to determine the nature of functioning and prospects for further development of the Ukrainian housing market.Â Â